2002
DOI: 10.20467/1091-5710.6.2.38
|View full text |Cite
|
Sign up to set email alerts
|

The Art and Science of Whole-Person Caring: An Interdisciplinary Model for Health Care Practice

Abstract: The art and science of whole-person caring is an interdisciplinary model that serves as a model for health care organizations to help create a healing and nurturing environment for consumers and health care personnel. This model is derived from theorists in the fields of nursing, physics, and systems theory. It is a practical and easily understood model that appeals to individuals and organizations interested in creating a sense of meaning and purpose within the health care environment. Personnel from all disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…The current study and the above study suggest that an intervention may be able to increase spiritual well-being. The findings of the current study also support previous nursing literature that reported that feeling love is part of spirituality and increased meaning (Goldberg, 1998;Krebs, 2001;Thornton, Gold, & Watkins, 2002).…”
Section: Between-groups Findingssupporting
confidence: 89%
“…The current study and the above study suggest that an intervention may be able to increase spiritual well-being. The findings of the current study also support previous nursing literature that reported that feeling love is part of spirituality and increased meaning (Goldberg, 1998;Krebs, 2001;Thornton, Gold, & Watkins, 2002).…”
Section: Between-groups Findingssupporting
confidence: 89%